Histological Evidence of Pollution-Induced Liver Damage in Fish: Comparative Analysis of Shatt Al-Basrah Canal and East Hammar Marsh Ecosystems - Abduljabbar, Sura K. Abduljabbar; Alsudani, Habeeb M. Alsudani M.; Abed, Jassim M. Abed M.; Larkin, Daniel J. Larkin J. (Sulaimani Journal for Humanities, 2025)
Comparative study of liver tissue from two fish species (Oreochromis niloticus [Nile tilapia] and Planiliza suviridis [greenback mullet]) in Shatt Al-Basrah Canal and East Hammar Marsh in southern Iraq revealed striking differences in liver health. Species from the environmentally degraded Shatt Al-Basrah Canal exhibited pronounced histological alterations, including cellular damage, inflammation, and necrosis, likely attributable to pollution and poor water quality in this aquatic system. In addition, fish hepatocytes from Shatt Al-Basrah Canal showed degenerative changes and pronounced nuclear damage, indicating impaired liver function. In contrast, fish from East Hammar Marsh, a more stable environment with better water quality, displayed healthy liver tissue, characterized by normal structural architecture. This comparative analysis highlights the influence of environmental factors on liver health and shows the utility of this multi-species histological approach for assessing environmental pollution.
Keywords: Liver histology; environmental pollution; Oreochromis niloticus; Planiliza suviridis; Shatt AlBasrah Canal; East Hammar Marsh